Disability, fatigue, pain and their associates in early diffuse cutaneous systemic sclerosis: the European Scleroderma Observational Study. (30th November 2017) - Peytrignet, Sébastien; Denton, Christopher P; Lunt, Mark; Hesselstrand, Roger; Mouthon, Luc; Silman, Alan; Pan, Xiaoyan; Brown, Edith; Czirják, László; Distler, Jörg H W; Distler, Oliver; Fligelstone, Kim; et al.
Abstract: Objectives: Our aim was to describe the burden of early dcSSc in terms of disability, fatigue and pain in the European Scleroderma Observational Study cohort, and to explore associated clinical features. Methods: Patients completed questionnaires at study entry, 12 and 24 months, including the HAQ disability index (HAQ-DI), the Cochin Hand Function Scale (CHFS), the Functional Assessment of Chronic Illness Therapy-fatigue and the Short Form 36 (SF36). Associates examined included the modified Rodnan skin score (mRSS), current digital ulcers and internal organ involvement. Correlations between 12-month changes were also examined. Results: The 326 patients recruited (median disease duration 11.9 months) displayed high levels of disability [mean (s .d .) HAQ-DI 1.1 (0.83)], with 'grip' and 'activity' being most affected. Of the 18 activities assessed in the CHFS, those involving fine finger movements were most affected. High HAQ-DI and CHFS scores were both associated with high mRSS (ρ = 0.34, P < 0.0001 and ρ = 0.35, P < 0.0001, respectively). HAQ-DI was higher in patients with digital ulcers ( P = 0.004), pulmonary fibrosis ( P = 0.005), cardiac ( P = 0.005) and muscle involvement ( P = 0.002). As anticipated, HAQ-DI, CHFS, the Functional Assessment of Chronic Illness Therapy and SF36 scores were all highly correlated, in particular the HAQ-DI with the CHFS (ρ = 0.84, P < 0.0001). Worsening HAQ-DI over 12 months was strongly associated with increasing mRSS (ρ = 0.40, P < 0.0001), decreasing hand function (ρ = 0.57, P < 0.0001) and increasing fatigue (ρ = −0.53, P < 0.0001). Conclusion: The European Scleroderma Observational Study highlights the burden of disability in early dcSSc, with high levels of disability and fatigue, associating with the degree of skin thickening (mRSS). Impaired hand function is a major contributor to overall disability.